On the Ehrenfest Paradox in the Bohr Atomic Model toward the Quantization of Gravitation - Fima Ardianto Putra (Department of Physics Universitas Gadjah Mada, 2020)
Ehrenfest Paradox has been studied in the Bohr Atomic Model as the theoretical procedure such a way that we can express the coordinate curvature i.e. gravitational aspect in the electromagnetic coupling constant. The strength of the curvature depends on the principal quantum number which shows that the value of curvature is quantized. For , the value is . The curvature value in the Bohr atomic model can be a standard to measure how strong the curvature of all system are, by comparing them with this value. We also get the understanding that the change of the curvature will manifest the curvature propagation in the form of quantum energy, i.e. . This theory can be considered to enlarge the unification theory between quantum and gravitation. Another consequence of this theory is the quantization of Equivalence Principle.